Discussion—A Note on the Optimal Depletion of Inventory - Derman, C.; Klein, M. (Management Science, 1959)
Authors' further comments and examples following their paper (Derman, C., M. Klein. 1958. Inventory depletion management. Management Sci. 4 (4, July).).